Neuropharmacological Actions of Metformin in Stroke - Jia, Jia; Cheng, Jian; Ni, Jingshu; Zhen, Xuechu (Current Neuropharmacology, 2015)
Increasing epidemiologic evidence suggests that metformin, a well-established AMPK activator and the most favorable first-line anti-diabetic drug, reduces stroke incidence and severity. However, the mechanism for this remains unclear. Moreover, previous experimental studies have reported controversial results about the effects of metformin on stroke outcomes during the acute phase. However, recent studies have consistently suggested that AMPK-mediated microglia/macrophage polarization and angioneurogenesis may play essential roles in metformin-promoted, long-term functional recovery following stroke. The present review summarizes the neuropharmacological actions of metformin in experimental stroke with an emphasis on the recent findings that the cell-specific effects and duration of AMPK activation are critical to the effects of metformin on stroke outcomes.
Keywords: AMPK activation